Electrosurgery on Giant Condyloma Acuminata - Agita Danaparamita Dharsono; Lita Setyowatie (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
Giant Condyloma Acuminata (GCA) is a sexually transmitted infection caused by Human papillomavirus (HPV) types 6 and 11. GCA lesions can growth up to 10 cm and form like a cauliflower shape. This infection can affect patient’s quality of life. The goal of therapy in GCA is to remove all skin lesions, which can be done by surgical treatment. Many modalities have been tested in GCA cases, one of which is electrosurgery. The aim of this study was to evaluate effectiveness of electrosurgery for GCA. A 43-year-old woman came with complaints of warts appeared in the genital area since 3 months before. Examination showed multiple papules with a verrucous surface, size around 7 cm in the labia majora, labia minor and perineum. The acetowhite examination and histopathology lead to the diagnosis of condyloma acuminata. Electrosurgery (electrodesication) to remove GCA lesions divided into 2 times. Post-operative evaluation, patient did not complain of pain and erythema, edema, and pus. Electrosurgery is a therapeutic modality that can be chosen in cases of GCA. Electrosurgery, like other surgical modalities, is capable of removing the entire lesion, but the advantages of electrosurgery include not injuring large areas, minimal bleeding and a lower recurrence rate when compared to other therapeutic modalities.